(untitled) (Fiep Bulletin - online, 2013)
To establish associations between cardiorespiratory fitness (VO ), with hypertension in adolescents. Method: 2max The sample of 324 girls and 208 boys, aged 9 throw 19 years. Body weight and height were measured. O VO was estimated at 2max 20 m test proposed by Léger. Blood pressure (BP) was measured using a sphygmomanometer the column of mercury. It was considered hypertension percentile 95o. Statistical analysis was usedbinary logistic regression, with p< 0.05. Results: There wasn’t significant association between cardiorespiratory fitness (VO ) and blood pressure in our study. Conclusion: 2 max Cardiorrespiratory fitness and hypertension show little conclusive relationship.